User Interface Aplikasi Pencegahan dan Penanganan Kekerasan Seksual di IT Telkom Purwokerto - Cahyo, Rangga (Fakultas Seni Rupa dan Desain ITB, 2024)
Since 2015 until 2022, there has been a surge in cases of sexual violence in the educational environment. Based on data compiled from SIMFONI PPA (Online Information System for the Protection of Women and Children), approximately 21,000 cases of sexual violence were recorded in the educational environment in 2022. This violence also occurs in the realm of higher education, and unfortunately, the handling of sexual violence in higher education institutions still relies on manual methods, leading to convoluted processes. As a result, very few victims report incidents due to the complexity of reporting and the sluggishness of the handling process. There is a need for action to address this issue, one of which is designing an application as a platform for addressing sexual violence. This research aims to design a user interface for an application to address sexual violence in higher education institutions in Indonesia using the design thinking method. The subjects involved are the academic community of IT Telkom Purwokerto as samples. In the testing, it was found that the application design created can help accommodate the needs of victims in the process of addressing sexual violence. This design is expected to serve as a blueprint for addressing sexual violence in higher education.